Investigation of hydrogen-bonding mediated molecular packing of diketopyrrolopyrrole based donor-acceptor oligomers in the solid state. (3rd January 2019) - Yang, Kun; Li, Xiang; Huang, Yi-Fan; Bhatta, Ram S.; Liu, Jiawei; Tsige, Mesfin; Wang, Chien-Lung; Cheng, Stephen Z.D.; Zhu, Yu
Abstract: Two diketopyrrolopyrrole (DPP)-based donor-acceptor oligomers with thermal labile 2-methylhexyl-2-oxylcarbonyl (mHoc) groups, mHocPBT and mHocTBT, were synthesized and characterized to study the hydrogen-bonding mediated molecular packing in solid state. The soluble oligomers can be converted to strong intermolecular hydrogen-bonded and pigment-like materials HPBT and HTBT by annealing the casted solid film at a temperature between 180 and 200 °C. The formation of intermolecular hydrogen bonding significantly altered the conformation of the molecules, molecular packing structure and related optical properties of the oligomers, with HPBT molecule exhibiting bathochromic shift and HTBT molecule exhibiting hypsochromic shift on UV/Vis spectra. Spin-casted mHocTBT and HTBT films also exhibited interesting morphology and charge transport properties. Even though the single mHocTBT oligomer molecule has a better coplanar molecular conformation as compared with that of HTBT, an enhanced π-π stacking structure and larger crystal grain size rendered HTBT film better charge transport performance. Graphical abstract: Highlights: Intermolecular hydrogen bonded networking was obtained via annealing of diketopyrrolopyrrole (DPP)-based oligomers. Molecular conformation, packing structure and optical properties of oligomers were elucidated before and after annealing. Morphology and charge transport properties of DPP oligomers were characterized before and after hydrogen bonding formation.